Investigative and the Rule of Law: A Cameroonian and Ukrainian Criminal Proceedings Law Understanding - Nguindip, Nana Charles; Mohilevskyi, Leonid Volodymyrovych; Yevhenovych, Ablamskyi Serhii; Kuzubova, Tetiana (Jurnal Cita Hukum, 2021)
There is no instance in a given society that can successfully operate and function without respecting existing standards and principles set in place in ensuring the respect of fundamental human rights and dignity. Cameroon and Ukraine have engaged huge steps in establishing credible laws, all in the preservation and protection of the fundamental human right of those presumed of the crime commission. This article establishes that the only way the rule of law can be respected during the investigative stage, will only when those responsible for investigation respects the due process of the law in the course of its investigation so that them act should not contravene the right of the suspect or accused in question. It provides that when issues of investigation are carried out by Ukraine and Cameroon police, gross violations of the criminal process are always experienced, and this greatly affects the objective of criminal law is that of protecting the right and dignity of everyone irrespective of the status quo acquired during the criminal proceedings. The results of this gross violation of the accused rights and status during the investigative stage will affect the rationale and objective of the criminal law system which is to ensure that all criminal processes should respect human standards and dignity. The reason for this is that, during the investigative process and procedure, the law enforcement officers must be able in detaching their various duties assigned with due diligence and respect to the various criminal standards of investigation. To ensure that this is done, there is that need of those enforcing the judicial process and trial should that all evidence, searches, seizures, recording done by the investigative police officials should be done in accordance of the free will of the presumed criminal.Keywords: investigative police, pretrial proceedings, observation, rule of lawInvestigasi dan Rule of Law: Pemahaman Hukum Acara Pidana Kamerun dan Ukraina AbstrakTidak ada contoh dalam masyarakat tertentu yang dapat berhasil beroperasi dan berfungsi tanpa menghormati standar dan prinsip yang ada yang ditetapkan dalam memastikan penghormatan terhadap hak asasi manusia dan martabat yang mendasar. Kamerun dan Ukraina telah melakukan langkah-langkah besar dalam menetapkan undang-undang yang kredibel, semuanya dalam pelestarian dan perlindungan hak asasi manusia yang dianggap sebagai komisi kejahatan. Pasal ini menetapkan bahwa satu-satunya cara penegakan hukum dapat dihormati selama tahap penyidikan, hanya jika mereka yang bertanggung jawab atas penyidikan menghormati proses hukum dalam proses penyidikannya sehingga tindakan mereka tidak boleh bertentangan dengan hak penyidik atau tersangka yang bersangkutan. Hal ini mengatur bahwa ketika masalah investigasi dilakukan oleh polisi Ukraina dan Kamerun, pelanggaran berat proses kriminal selalu dialami, dan ini sangat mempengaruhi tujuan hukum pidana adalah melindungi hak dan martabat setiap orang terlepas dari status quo diperoleh selama proses pidana. Akibat dari pelanggaran berat terhadap hak dan status terdakwa selama tahap penyidikan akan mempengaruhi dasar pemikiran dan tujuan dari sistem hukum pidana yaitu untuk menjamin bahwa semua proses pidana harus menghormati standar dan martabat manusia. Pasalnya, selama proses dan prosedur penyidikan, aparat penegak hukum harus mampu melepaskan berbagai tugas yang diberikan dengan kehati-hatian dan menghormati berbagai standar pidana penyidikan. Untuk menjamin hal itu dilakukan, maka perlu bagi para penegak proses peradilan dan persidangan bahwa semua barang bukti, penggeledahan, penyitaan, pencatatan yang dilakukan oleh penyidik polisi harus dilakukan sesuai dengan kehendak bebas dari tersangka pidana.Kata Kunci: Penyidik Kepolisian; Proses Praperadilan; Pengawasan; Supremasi Hukum Розслідування та верховенство права: розуміння камерунського та українського кримінального процесуАнотаціяУ суспільстві не існує жодного прикладу, який міг би успішно оперувати і функціонувати без дотримання існуючих стандартів і принципів, встановлених для забезпечення поваги основних прав і гідності людини. Камерун та Україна зробили величезні кроки у створенні надійних законів щодо збереження та захисту основних прав людини, в тому числі для осіб, які скоїли злочин. Встановлено, що єдиним способом дотримання верховенства права на стадії розслідування є належне додержання особою, яка здійснює розслідування, процесуального права. Однак, як свідчать практичні реалії, під час розслідувань спостерігаються порушення поліцією процесуального закону, що значною мірою впливає на мету кримінального процесу, яка полягає в захисті права та гідності кожного, незалежно від статус-кво, отриманого під час кримінального провадження. Результати грубого порушення прав на стадії розслідування також можуть впливати на логіку та завдання кримінального процесу, яка полягає в тому, щоб усі системи кримінального судочинства поважали людські стандарти та гідність. Причина цього полягає в тому, що під час кримінального процесу працівники правоохоронних органів повинні мати можливість відокремити свої різні обов’язки, покладені на них, з належною ретельністю та дотриманням різних кримінальних стандартів розслідування. Для забезпечення цього необхідно, щоб особи, які забезпечують виконання судового процесу та судового розгляду, усі докази, обшуки, виїмки, записи, зроблені працівниками поліції, досліджвали незалажно від волевиявлення підозрюваного, обвинуваченого.Ключові слова: слідча поліція, досудове провадження, спостереження, верховенство права.